O pensamento de máquinas em Ada Lovelace: The machine thinking in Ada Lovelace (Simbiótica. Revista Eletrônica, 2023)
To construct machines that simulate human actions has a wide expression on Modernity with the increasing interest to understand how people work through construction of the automaton. Into this context the problem of thinking of machines is located in Ada Lovelace, a mathematician in nineteenth century, in England. Then the objective of this paper is to elucidate Ada’s answer regarding the problem if machines are able to think. To Ada, machines do not think. Since it, we try to demonstrate that the Turing’s argument against Ada do not consider fundamental elements from dualism of substances paradigm. This Turing’s disregard points to a significant technological change and human perspective into a period of one century that separates him and Ada.